Architecture and service model of IoT enabled platform - Zhao PENG (Dianxin kexue)
Existing successful IoT (internet of things) application cases concentrate on the vertical field of local scale and usually focused on closed loop applications,which leading to numerous application islet.Internet companies,traditional equipment manufacturers,cloud service providers,as well as other industrial giants have built an IoT ecosystem with the core of its own capabilities.Starting with key point of building IoT ecosystem,technology architecture and service model of IoT enabled platform was studied,the core function and key technology of platform was discussed,and the platform development trend was presented.